Myocardial contraction fraction predicts mortality in the oldest old. (December 2022) - Leibowitz, David; Bishara, Yara; Stessman-Lande, Irit; Hammerman-Rosenberg, Aliza; Jacobs, Jeremy M.; Gilon, Dan; Stessman, Jochanan
Abstract: Background: People over the age of 85 are the world's most rapidly growing age group. Ejection fraction (EF) may be limited prognostically in this population and myocardial contraction fraction (MCF) may be more accurate. The objective of this longitudinal study was to assess the prognosis of MCF in an age-homogenous, community-dwelling population of subjects. Methods: Subjects were recruited from the Jerusalem Longitudinal Cohort Study. Echocardiography was performed with a portable echocardiograph at the subjects place of residence. Standard echocardiographic assessment of cardiac structure and function including MCF was performed. Values of EF and MCF above and below the median for males and females were defined as normal and abnormal in categorical analysis. 5-year mortality was assessed via a centralized government database. Results: 418 subjects (199 males, 219 females) were enrolled in the study of whom 113 (27 %) died at the time of 5-year follow-up. Subjects who died had significantly lower MCF (32 ± 14 % vs 36 ± 12 %; p < 0.004) and EF (51.6 ± 11.6 % vs 56.3 ± 9.4 %; p < 0.0001) than survivors. The association between MCF and mortality remained significant on clinical multivariate analysis as both a categorical and continuous variable while EF was only significant as a continous variable. When both EF and MCF were added to the model only MCF as a categorical variable remained significant. Conclusions: MCF assessed by home echocardiography provides additional prognostic information to EF and may be a superior predictor of 5-year mortality in a community-dwelling population of the oldest old.